2013
DOI: 10.1007/s00122-013-2139-0
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping of salt tolerance in barley (Hordeum vulgare L.)

Abstract: A spring barley collection of 192 genotypes from a wide geographical range was used to identify quantitative trait loci (QTLs) for salt tolerance traits by means of an association mapping approach using a thousand SNP marker set. Linkage disequilibrium (LD) decay was found with marker distances spanning 2-8 cM depending on the methods used to account for population structure and genetic relatedness between genotypes. The association panel showed large variation for traits that were highly heritable under salt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 81 publications
7
111
0
Order By: Relevance
“…The QTLs located on 4H (4.61 cM) and 6H (11.97 cM) had positive effect under 1000 ppm conditions. These results are close to those obtained by Long et al (2013) where they detected five QTLs associated with chlorophyll contents on chromosomes 1H (31.cM), 5H (6.4 cM), 6H (45.4 and 60.2 cM) and 7H (4.9 cM). In addition, they reported that genomic region on chromosome 6H strongly influenced ST as well as chlorophyll content.…”
Section: Rwc and CCsupporting
confidence: 90%
See 3 more Smart Citations
“…The QTLs located on 4H (4.61 cM) and 6H (11.97 cM) had positive effect under 1000 ppm conditions. These results are close to those obtained by Long et al (2013) where they detected five QTLs associated with chlorophyll contents on chromosomes 1H (31.cM), 5H (6.4 cM), 6H (45.4 and 60.2 cM) and 7H (4.9 cM). In addition, they reported that genomic region on chromosome 6H strongly influenced ST as well as chlorophyll content.…”
Section: Rwc and CCsupporting
confidence: 90%
“…Furthermore, the latter QTL explained 25.67% of the genetic variance in 7H (125.4 cM), while the other QTLs had negative main effect. These results are in harmony with those obtained by Long et al (2013) where they detected QTLs for Na + , K + content on chromosome 4H and 7H. Shavrukov et al (2010) detected a QTL for Na + , K + and Na + /K + ratio locates near the center of chromosome 7H and this might be related to the HvNax3 locus.…”
Section: Nasupporting
confidence: 87%
See 2 more Smart Citations
“…QTL-QY4 at 4H was also co-located with a MQTL for salt tolerance, strengthening this further. QTL-QY5, with a LOD peak value of 55 cM, is located close to a QTL controlling salt tolerance found by Long et al (2013) that co-localised with biomass growth, chlorophyll content and leaf senescence. They used association mapping of 192 barley cultivars from all over the world, including 92 cultivars from Europe.…”
Section: Discussionmentioning
confidence: 79%